Hypertension as Risk Factor of Poor Functional Outcome in Primary Ischemic Stroke Patients - Siti Aisyah Affiati; Astuti Prodjohardjono; Abdul Gofir; Probosuseno Probosuseno; Noor Alia Susanti; Sri Sutarni; Ismail Setyopranoto (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
Survival rate of ischemic stroke has been improving which increases long-term disability in consequences. GBD 2017 shows stroke as the third most common cause of morbidity. Hypertension is the most common risk factor for ischemic stroke incidence and affecting long-term functional outcome. Therefore, hypertension control in ischemic stroke is expected to improve functional outcome and quality of life. Therefore, this study was conducted to know the role of hypertension as risk factor of poor functional outcome in primary ischemic stroke patients. Study was conducted by observational retrospective cohort from May 2018 until April 2019 in 7 hospitals in D.I. Yogyakarta. Functional outcome of primary ischemic stroke patients was assessed by physician at day 30 by using Barthel Index. Bivariate analysis was analyzed by using Chi-Square with 95% CI and p-value <0.05 indicated statistical significance. Based on the study, there were increased risk for having dependent functional outcome in hypertension (RR=1.12, 95% CI=0.74-1.69), diabetes mellitus (RR=1.041, 95% CI=0.71-1.53) but these results were not statistically significant (p>0.05). From the study it can be concluded that hypertension is one of the most common risk factors of stroke but hypertension has no role in predicting functional outcome. However, hypertension increases risk for having poor functional outcome in ischemic stroke patients.